The effect of Avocado leaf extract (Persea americana Mill.) on the fibroblast cells of post-extraction dental sockets in Wistar rats - Christian Khoswanto; Wisnu Setyari Juliastuti; Karina Awanis Adla (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Tooth extraction, a common practice among the dental profession, causes trauma to the blood vessels during the wound healing process. The acceleration of wound healing, within which fibroblasts play an important role, is influenced by nutrition. Avocado leaves contain a variety of chemicals, including flavonoid compounds, tannins, katekat, kuinon, saponin and steroids/triterpenoid. Avocado leaves also contain glycosides, cyanogenic, alkaloids and phenols which function as anti-inflammatory, antibacterial and antioxidant agents. This avocado leaf content could be used as an alternative medicine to accelerate the wound healing process in post-tooth extraction sockets. Purpose: To determine the role of avocado leaves (Persea americana Mill) in accelerating fibroblast cells proliferation in tooth socket post-extraction. Methods: The sample was divided into four groups, a control group and three treatment groups. The treatment groups used avocado leaf extract and 3% CMC Na solution which was inserted into the tooth sockets of Wistar rats. Both the control and treatment groups had their mandibula decapitated with all the required specimens being prepared on the 3rd and 7th days of the experiment. Mandibular decapitation and tooth extraction socket were prepared by HPA (Histology Pathology Anatomy) with Hematoxylin Eosin (HE) staining. The  fibroblast proliferation was analyzed by means of a light microscope at 400x magnification. The obtained data was analyzed using a t-Test. Result: The t-Test obtained a significance value 0.001 (p <0.05) between the control and treatment groups. The number of fibroblast cells increased in the group treated on the third day and decreased in the group treated on the seventh day. Conclusion: Avocado leaf extract (Persea americana Mill.) accelerates proliferation of fibroblast cells in Wistar rats post-tooth extraction.